CBCT imaging – A boon to orthodontics - Genevive L. Machado (Saudi Dental Journal)
The application of innovative technologies in dentistry and orthodontics has been very interesting to observe. The development of cone-beam computed tomography (CBCT) as a preferred imaging procedure for comprehensive orthodontic treatment is of particular interest. The information obtained from CBCT imaging provides several substantial advantages. For example, CBCT imaging provides accurate measurements, improves localization of impacted teeth, provides visualization of airway abnormalities, it identifies and quantifies asymmetry, it can be used to assess periodontal structures, to identify endodontic problems, to plan placement sites for temporary skeletal anchorage devices, and to view condylar positions and temporomandibular joint (TMJ) bony structures according to the practitioner’s knowledge at the time of orthodontic diagnosis. Moreover, CBCT imaging involves only a minimal increase in radiation dose relative to combined diagnostic modern digital panoramic and cephalometric imaging. The aim of this article is to provide a comprehensive overview of CBCT imaging, including its technique, advantages, and applications in orthodontics. Keywords: Cone beam computed tomography, Orthodontic applications